Pronounced antiepileptic activity of the subtype‐selective GABAA‐positive allosteric modulator PF‐06372865 in the GAERS absence epilepsy model. (12th August 2018) - Duveau, Venceslas; Buhl, Derek L.; Evrard, Alexis; Ruggiero, Céline; Mandé‐Niedergang, Betty; Roucard, Corinne; Gurrell, Rachel
Summary: Aim: Antiepileptic drugs that modulate GABA have the potential to aggravate or improve the symptoms of absence epilepsy. PF‐06372865 is a positive allosteric modulator (PAM) of α2/3/5 subunit‐containing GABAA receptors with minimal activity at α1‐containing receptors, which are believed to mediate many of the adverse events associated with benzodiazepines. The aim of this study was to assess the antiepileptic effect of PF‐06372865 in a preclinical model of absence seizures. Methods: Genetic absence epilepsy rats from Strasbourg (GAERS) was implanted with four cortical electrodes over the frontoparietal cortex, and the number and cumulated duration of spike‐and‐wave discharges (SWDs) were recorded for 10‐90 minutes following administration of vehicle, PF‐06372865, and positive controls diazepam and valproate. Results: PF‐06372865 (0.3, 1, 2, 10 mg kg −1 ) dose‐dependently reduced the expression of SWDs, including full suppression at the highest doses by 30 minutes after administration. Conclusions: PF‐06372865 demonstrated robust efficacy in suppressing SWDs in the GAERS model of absence epilepsy. To our knowledge, this is the first demonstration of antiepileptic activity of an α2/3/5‐subtype‐selective GABAA PAM in a model of absence epilepsy. Further study of the antiepileptic properties of PF‐06372865 is warranted in patients with absence seizures.